NET-1 promotes invasion, adhesion and growth of hepatocellular carcinoma by regulating the expression of BAX, caspase 3, caspase 8 and BCL2 - Wang, Mingchun; Sun, Xiangjun; Jiang, Yongjun; Tan, Zhen (Cellular and Molecular Biology, 2018)
Dysregulation of neuroepithelial transforming gene-1 (NET-1) has been shown in hepatocellular carcinoma (HCC) patients. We aimed to evaluate the influence of NET-1 on HCC invasion, adhesion and growth. In vitro cellular functional assays including invasion and adhesion were performed to evaluate the effects of knockdown and overexpression of NET-1. HCC cells were transplanted into nude mice, and tumor growth was assessed. BAX, caspase 3, caspase 8 and BCL2 protein levels were detected by western blot. After transfection with NET-1 siRNA, NET-1 positive ratio in HCC cells significantly decreased. Cell invasion and adhesion assay showed that knockdown of NET-1 reduced the invasion and adhesion ability of HCC cells, whereas overexpression of NET-1 increased the ability. The evaluation of tumor growth revealed that NET-1 knockdown significantly decreased tumor volume and weight, while NET-1 overexpression promoted tumor growth in nude mice. Western blot showed that NET-1 knockdown increased BAX, caspase 3 and caspase 8 expression but decreased BCL2 expression, whereas NET-1 overexpression significantly down-regulated BAX, caspase 3 and caspase 8 expression but increased BCL2 expression. Our data suggest that NET-1 promotes HCC invasion, adhesion and growth by regulating BAX, caspase 3, caspase 8 and BCL2 expression.